The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1097/brs.0b013e3181844ef2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Intrathecal Morphine After Posterior Lumbar Interbody Fusion Surgery

Abstract: We demonstrated the efficacy of 0.4 mg intrathecal morphine after PLIF-surgery as indicated by a significantly lower cumulative piritramide requirement without any serious increase of opioid associated side effects. Therefore, morphine in a dose of 0.4 mg administered intrathecally seems to be a viable alternative therapeutic option to provide postoperative analgesia with PLIF-surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 33 publications
0
45
0
4
Order By: Relevance
“…A number of studies have focused on pain treatment in spine surgery, but most studies have focused on primary degenerative conditions in the lumbar spine treated with discectomy, decompression and lumbosacral fusion [10,11]. Since an increased number of major spinal procedures, including revision surgery can be anticipated, we found it of relevance to assess a multimodal pain treatment strategy in patients undergoing surgery requiring instrumentation on [3 levels.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have focused on pain treatment in spine surgery, but most studies have focused on primary degenerative conditions in the lumbar spine treated with discectomy, decompression and lumbosacral fusion [10,11]. Since an increased number of major spinal procedures, including revision surgery can be anticipated, we found it of relevance to assess a multimodal pain treatment strategy in patients undergoing surgery requiring instrumentation on [3 levels.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Local infiltration of anesthetics in the surgical site during wound closure is commonly performed with lumbar spine surgery. 8,9 These agents are traditionally used to provide postoperative analgesia, but the effects are limited by dosing restrictions due to potential systemic side effects from peak plasma concentrations. 10 Furthermore, the duration of analgesia is limited by each anesthetic's halflife.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial evaluating the effect of intraoperative epidural bolus of fentanyl during lumbar decompressive surgery, Guilfoyle et al reported lower early postoperative visual analogue scale (VAS) pain scores within the treated group but also an increased rate of urinary catheterization [49]. In a pair of randomized controlled trials, intrathecal morphine and fentanyl were demonstrated to decrease cumulative opioid demand in patients undergoing lumbar spinal surgery [50,51].…”
Section: Neuraxial Blockadementioning
confidence: 98%